2019
DOI: 10.1590/0104-6632.20190364s20190208
|View full text |Cite
|
Sign up to set email alerts
|

In situ DEPOSITION OF COPPER NANOPARTICLES ON POLYETHYLENE TEREPHTHALATE FILTERS AND ANTIBACTERIAL TESTING AGAINST Escherichia coli AND Salmonella enterica

Abstract: This study reports a synthesis of copper nanoparticles (CuNP) deposited on polyethylene terephthalate (PET) filters and antibacterial evaluation of the obtained filters against Escherichia coli and Salmonella enterica. CuNP were synthesized by a two-step method involving adsorption of [Cu(OH) 4 ] 2ions onto a PET filter and subsequent chemical reduction by ascorbic acid without using other capping agents. The synthesized CuNP were 105±26 nm (mean±SD) in size and agglomerated into clusters on the PET fibres. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In hybrids PET-inorganic bactericides representative are: PET-Ag nanoparticles [60][61][62][63][64][65][66][67], PET-silver salts [68,69], PET-TiO 2 [70][71][72][73], PET-Zn/ZnO 2 [74][75][76][77] and/or PET-Au [78]. In the set of PET-metal hybrids only a few PET-Cu hybrids have been reported [79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…In hybrids PET-inorganic bactericides representative are: PET-Ag nanoparticles [60][61][62][63][64][65][66][67], PET-silver salts [68,69], PET-TiO 2 [70][71][72][73], PET-Zn/ZnO 2 [74][75][76][77] and/or PET-Au [78]. In the set of PET-metal hybrids only a few PET-Cu hybrids have been reported [79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…Jeyaraj et al ( 2015 ) suggest that the acid chemical treatment cleans the fiber before the impregnation of natural dyes. For a concentrated alkaline medium, Nguyen et al ( 2019 ) suggested that the chemical pretreatment in PET filters leads to a mass loss, degrading the fiber due to the concentrated medium.…”
Section: Resultsmentioning
confidence: 99%
“…In KOH solutions, PET is partially hydrolyzed into soluble ethylene glycol, potassium terephthalate, and short-chain fragments, hence reducing the weight of the filter and forming the holes on the PET fiber surface (Figure 4). These holes, where the polymer was hydrolytically cleaved, contain carboxylate and hydroxyl groups which may interact and bind copper ions more effectively than the untreated fiber surface [16].…”
Section: Resultsmentioning
confidence: 99%